The Role of Energy Supply in Economic Growth: Evidence from the Oil Importing Countries - Samawi, Ghazi A.; Mdanat, Metri F.; Arabiyat, Talah S. (International Journal of Energy Economics and Policy, 2017)
The main purpose of this study is to explore and analyse relationships between energy supply and economic growth. Path analysis and structural equation modelling have been used to analyse the direct and indirect effects of energy supply on economic growth by identifying the form of the relationships between them and the role of mediating variables. Energy supply was found to be strongly correlated with economic growth and to have a number of other relationships and effects on the economy. It was also found that mediating variables had different relationships and effects on the economy based on the source of energy. This result confirms that changes in energy suppliers seem to reflect changes in the political ‎economy of the country rather than shifts in energy use. The influence of the ‎political economy and the preferential treatment of supplying energy to oil importing countries below ‎market price were found to have mixed effects on economic growth for both trade and budget path models.‎ Keywords: Energy supply, Economic growth, Structural equation, Path analysis. ‎ JEL Classifications: Q41, O4, Q43, C32. ‎